(untitled) (Research, Society and Development, 2020)
The fleet maintenance sector represents a large part of the costs in agro-industrial properties and all the innovation and technology used to reduce these costs directly impacts the final price of the product. Given this context, the objective of this article is to identify how the state of knowledge about predictive maintenance tools for diesel engines is configured. To meet the objective, a systematic bibliographic review was used, consisting of three phases: Input, Processing and Output. It was possible to identify an advance in scientific production related to predictive maintenance tools, which reinforces its importance. When analyzing the documents in full, it was possible to categorize the documents by applicability, being: Industrial; Diesel Engines; 2T Diesel Engines; Diesel Engines for Agricultural Tractors; Engines and Mechanical equipment; Bus and Passenger Transport; Mining and Maritime. It was also possible to conclude that the sectors that research and develop the most predictive maintenance tools for engines are industrial and marine. Of the 41 documents analyzed in this research, eight are book chapters, which demonstrates that the analysis of such a documentary format is relevant to the theme addressed here. Likewise, research on predictive maintenance has been gaining importance in recent years, which leads us to believe that it must also move towards the agricultural sector.